Tradução técnica: da composição lexical à constituição do discurso - Mazza, Luciene Novais (2015)
Into the corporate world there are various standard settlement documents establishing an explicit hierarchy of power with respect to the effectiveness of written texts, invoking actors by a specific mode of enunciation in the process of translating a text from a given source language into a target language. But, despite that rigid regulation could be homogenized, in terms of meaning, it has not prevent cultural dimension interference that reflects the foreign text and also it cannot obscure the value of diversity amongst companies spread all over the world. On the other hand, that interference has effects on the way to develop writing of domain-specific language even in English as the global language of business. Besides the identity preserved by regulations and standards, this thesis aims to demonstrate differences on translating a technical document from multiple foreign languages into English. The starting point for our research lies in three main approaches: the translation process, highlighting the linguistic and cultural diversities amongst target texts; Bakhtin´s theory of dialogical discourse on the concept of multiple voices, the plurivocity as a fundamental condition operating the meaning; terminology studies that provides a theoretical and methodological bases to search for lexical units in a specific domain. Moreover, the theory and corpus-based studies allow developing an initial methodological procedure based on corpus linguistics analysis, considering the three aspects: (i) lexical variation leveling of its irregularities and further establishing identity amongst texts, (ii) linguistics invariant enabling to recognize the differences within groups as well as enunciative traces in which discourse are addressed to take place in different social and cultural environment, (iii) effects of relationship of lexical units among texts so as to provide a normalization and standardization of compound words (terms) that are given in specific contexts. This research in a relevant sense finds support on a study-initiated of a previous master´s program. In addition to it offers knowledge carried out under particularly specific features of linguistics and social scope to pharmaceutical domain and also issues relate to corporate interests and its interdisciplinary scientific fields